Green CITYnomics : the urban war against climate change. - Tang, Kenny, ....- (Sheffield : Greenleaf, 2009)
Today, more than half of the world's population are living in cities that are now contributing 80 per cent of global greenhouse gas emissions. They cover less than 3 per cent of the earth's surface. And urbanisation continues apace. With such a massive carbon footprint, it is clearly vital that cities are part of the solution. And, from another perspective, the sheer concentration of people, resources and economic activities in urban centres will only serve to magnify city-dwellers' vulnerability to the effects of climate change. Despite this, to date scarcely any consideration has been given to the potential impact of climate change on urban dwellers, especially in the developing countries and burgeoning megacities of Africa, Asia and Latin America, where a wide variety of environmental and development challenges are likely to further exacerbate their vulnerability to climatic effects. Such population concentrations mean local decision-makers have both an opportunity and obligation to
Construct climate-resilient infrastructures, create climate-friendly livelihoods and develop urban systems that ensure better air quality, water, transport and health services for all who live in them. Environmental liabilities need to be transformed into sustainable assets. "Green CITYnomics: The Urban War against Climate Change" presents a rich set of contributions by a highly diverse group of 45 of the world's leading urban experts on climate change. In particular, it illustrates the desire some cities are already demonstrating in engaging in this war. Standing still is not an option. Budgets have to be fought for; minds have to be won over; old, untenable and unsustainable ideas and solutions must be challenged; and, green and sustainable solutions must be given the chance to develop and to prove themselves. The book is organised into four sections. First, contributors discuss the challenges of making an integrated assessment of the impact of climate change in our urban centres. Second
The book examines the options and challenges for policy-makers. Third, specific aspects of health, air quality, land use and water supply are examined. Finally, the focus moves to specific aspects of solar heating, urban heat island intensity, building emissions and urban planning education. Each of the cities and urban centres discussed - from Hong Kong to Dresden; from Mexico City to Qatar - are, in their own ways, heroes and examples to us all. This book provides a compelling manifesto for the world's cities in their 'Urban War against Climate Change'. It will be essential reading for climate scientists, national and local policy-makers and scholars worldwide.